The World of P: The Material Realm of Priestly Writings. - Faust, Avraham (Vetus Testamentum, 2019)
The Priestly source (P) is a common designation in scholarship for significant parts of the Pentateuch, which are assumed to have been written in priestly circles. While the social circles and theological background of P are more agreed upon, its dating is hotly debated, and various textual, intertextual, linguistic and historical evidence were employed in an attempt to date its composition. The present paper aims to examine the material world that is assumed by a number of Priestly texts, and the landscape in which the writings are embedded, in order to shed new light on their dating. The paper concludes that much of the priestly writings (inclusive of some of the texts commonly attributed to the Holiness school) are quite intelligible on the background the late Iron Age, mainly the 8th-7th centuries BCE.